Punishment of Medical Personnel and Health Workers in Malpractice Charges Based on Law Number 17 of 2023 Concerning Health - Yustinus Rurie Wirawan; Yasmirah Mandasari Saragih; Gunawan Wdjaja; Jahidin Kuswanto; Moch Nagieb (Riviera Publishing, 2026)
This study discusses the criminal liability of medical personnel based on Law No. 17 of 2023 concerning health in Indonesia. The background of this research is the increasing number of lawsuits against medical personnel due to rising public awareness of patient rights, as well as the legal uncertainty faced by medical personnel regarding malpractice. The aim of this research is to analyze the criteria for criminal negligence in medical services and to understand the legal protection mechanisms through the Professional Disciplinary Council and mediation to prevent the criminalization of medical personnel. This research employs a normative juridical method with statutory and conceptual approaches. The findings show that Law No. 17 of 2023 provides a clearer framework for the criminal accountability of medical personnel, emphasizing gross negligence and adherence to professional standards. The study also found that the recommendation mechanism from the Professional Disciplinary Council, along with the requirement for mediation, can help prevent baseless criminalization. In conclusion, this law provides better legal protection for medical personnel and reduces legal uncertainty in medical practice.